2019
DOI: 10.1175/jcli-d-18-0528.1
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Pattern of Midsummer Drought as a Possible Mechanistic Response to Lower-Tropospheric Easterlies over the Intra-Americas Seas

Abstract: Following the idea that large-scale wind perturbations cause repeatable rainfall patterns over small tropical islands, the spatial pattern of the midsummer drought (MSD) is investigated as a repeatable rainfall pattern over the Intra-Americas Seas (IAS). For that, statistical techniques, including linear regressions, canonical correlation analysis, and variance budgets, were applied to the Tropical Rainfall Measuring Mission and ERA-Interim datasets to assess 1) the MSD pattern repeatability and 2) its explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…The WT method proved useful to separate the wet season in each dataset into three stages: the first and second peak periods (P1 and P2) and the drier period (MSD). This approach was able to reproduce the so-called "MSD patterns" reported in previous studies (Zermeño-Díaz, 2019, Zhao et al, 2020 using various diagnostics such as OLR, ω and the low-level winds.…”
Section: The Role Of the Caribbean Low-level Jetmentioning
confidence: 80%
See 2 more Smart Citations
“…The WT method proved useful to separate the wet season in each dataset into three stages: the first and second peak periods (P1 and P2) and the drier period (MSD). This approach was able to reproduce the so-called "MSD patterns" reported in previous studies (Zermeño-Díaz, 2019, Zhao et al, 2020 using various diagnostics such as OLR, ω and the low-level winds.…”
Section: The Role Of the Caribbean Low-level Jetmentioning
confidence: 80%
“…The third hypothesis argues that the MSD is related to the CLLJ variability (Herrera et al, 2015, Zermeño-Díaz, 2019, Martinez et al, 2019. Synchronous changes to the zonal wind, the integrated moisture flux convergence (IMFC) and the precipitable water vapor suggest that the low-level wind flow in the Caribbean varies coherently with the stages of the MSD.…”
Section: The Role Of the Caribbean Low-level Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…Several roles have been attributed to the CLLJ to explain a link between the low-level wind flow over the Caribbean Sea and the MSD in southern Mexico and Central America (see e.g. Gamble et al 2008;Herrera et al 2015;Zermeño-Díaz 2019;Corrales-Suastegui et al 2020). The main dynamical argument that links the MSD and the CLLJ is centred around variations in moisture flux convergence (MFC), and would subsequently influence the mass content of water vapor or total water content (TWC) (see e.g.…”
Section: The Solar Declination Angle Hypothesismentioning
confidence: 99%
“…Since the early analyses of the characteristics of the MSD, research has aimed to understand the physical mechanisms that cause this peculiar two-peak structure of precipitation (e.g., Hastenrath 1967;Magaña et al 1999;Giannini et al 2000;Curtis 2002;Herrera et al 2015;Hidalgo et al 2015;Maldonado et al 2016;Zermeño-Díaz 2019). For instance, Hastenrath (1967) first suggested that a double-crossing of the east Pacific Intertropical Convergence Zone (ITCZ) can explain the MSD, so the first peak of precipitation is associated with the early summer northward crossing of the ITCZ and the second peak with the southward displacement of the ITCZ during late summer.…”
Section: Introductionmentioning
confidence: 99%